Electrical field distribution of Change-N1 and its prepulse inhibition. (23rd April 2021) - Watanabe, Takayasu; Motomura, Eishi; Kawano, Yasuhiro; Fujii, Shinobu; Hakumoto, Yuhei; Morimoto, Makoto; Nakatani, Kaname; Okada, Motohiro; Inui, Koji
Highlights: Change-N1 and its prepulse inhibition (PPI) were recorded by EEG. Change-N1 showed right predominance. There was no difference in %PPI among the electrode locations. The Change-N1 amplitude showed a positive correlation between frontal and prefrontal regions. The %PPI also showed a positive correlation between these two regions. Abstract: An abrupt change in a sound feature (Test) in a continuous sound elicits an auditory evoked potential, peaking at approx. 100–180 ms (Change-N1) after the change onset. Change-N1 is attenuated by a preceding weak change stimulus (Prepulse), in the phenomenon known as prepulse inhibition (PPI). In this electroencephalographic study, we compared these two indexes among scalp electrodes. Change-N1 was elicited by an abrupt 10-dB increase in sound pressure in repeats of a 70-dB click sound at 100 Hz and was recorded using 22 electrodes in 31 healthy subjects. The prepulse was a 10-dB decrease in three consecutive clicks at 30, 40, and 50 ms before the Test onset. Four stimuli (Test alone, Test with Prepulse, Prepulse alone, and background alone) were presented randomly through headphones at an even probability. The results demonstrated that: (1) Electrodes at the frontal/central midline were reconfirmed to be suitable to record Change-N1; (2) Change-N1 showed right-hemisphere predominance; (3) There was no difference in the %PPI among regions (prefrontal/frontal/central) and hemispheres (midline/left/right); and (4) the Change-N1 amplitude and its PPI at prefrontal electrodes were positively correlated with those at the frontal electrodes. These results support the use of Change-N1 and its PPI as a tool to evaluate the change detection sensitivity and inhibitory function in individuals. The use of prefrontal electrodes can be an option for a screening test.